Development, validation and implementation of an NGS gene panel approach for the diagnosis of renal amyloidoses - Fernandes, Ana Rita Albuquerque (2022)
Amyloidosis comprises a group of diseases whose pathogenesis is related with the deposition of amyloid fibrils in organs or tissues, disrupting their function and ultimately, leading to their failure. The different amyloidosis types can vary according to amyloid distribution (localised or systemic) and its origin (acquired or hereditary), both influenced by the precursor protein associated. Each precursor protein can be associated with two forms of distribution and origin, complicating the diagnosis. In fact, currently 36 different proteins can originate amyloid fibrils and their identification is fundamental in order to achieve a correct diagnosis. However, the elevated number of precursor proteins associated and the heterogeneous presentation of the disease often lead to misdiagnosis and incorrect treatments that can endanger patient’s lives. The evolution in amyloidosis diagnosis through the last few years has allowed the detection and treatment of the disease sooner, extending the patient’s survival. This fact is related to the introduction of new methodologies in the diagnostic workflow, such as mass spectrometry, which identifies the precursor protein using biopsy tissue, as well as NGS approaches which detects variants present in DNA extracted from blood, particularly important for genetic counselling of families affected with hereditary amyloidosis. In this dissertation, a new approach to study amyloidosis at CGMJM was developed, employing NGS methodologies, based on the design of a multi-gene panel including genes previously associated with amyloidosis. This approach was an attempt to improve amyloidosis diagnosis efficiency and associated costs, since the current CGMJM routine diagnostic workflow consists in consecutive single-gene analysis by conventional sequencing, which is time and resource consuming. Firstly, the NGS multi-gene panel was tested through double-blind assays, using control samples from patients who were previously molecularly diagnosed (positive controls). The disease-causing variants of the controls’ samples were correctly detected and a good coverage was obtained, enabling the validation of the designed NGS multi-gene panel. Afterwards, the NGS multi-gene panel was employed in DNA samples of genetically uncharacterized patients in an attempt to achieve a molecular diagnosis. Concurrently, in order to complement the study of these patients and apart from the NGS multi-gene panel design, primers targeting genes not previously included in the panel were designed for conventional sequencing, as well as primers to cover regions presenting low coverage using the NGS panel. This new study approach did not result in the detection of variants with reported pathogenicity. However, the amyloidosis NGS multi-gene panel efficiency in variant detection was confirmed. With this work, the availability of the amyloidosis NGS multi-gene panel as a first-tier approach in amyloidosis diagnosis has been demonstrated, enabling several samples sequencing and multiple target genes at the same time, particularly important in this disease associated with several protein precursors, increasing clinical efficiency and reducing diagnosis time and costs.